Governance on sustainability criteria in the argentinean automotive and autoparts global value chain and upgrading opportunities for SMES - Amato, Celina Noé (2024)
This paper looks at the influence of governance on the transmission and adoption of sustainability criteria in the Argentine automotive and autoparts global value chain (GVC), and the real possibility for local small and medium sized enterprises (SMEs) to achieve upgrading through these criteria. A qualitative research was conducted to which twenty-six people from fourteen different stakeholders from the GVC were interviewed for data collection. As conclusion, governance on sustainability criteria in the GVC manifests as multipolar than a captive one. The analysis showed there are many stakeholders influencing sustainability criteria, apart from the leading companies. Still, opportunities for sustainability upgrading are scarce for SMEs suppliers that do not supply to leading companies, which are at a clear disadvantage in terms of sustainability. Moreover, sometimes SMEs in a developing country even face sustainability downgrading that could neutralize the upgrading opportunities.